The Pakistan Studies Curriculum Role in Shaping Foreign Policy Perceptions - Ms. Nusrat Khaskheli; Ms. Najma Naz; Shafique Husssain Wassan (`, 2025)
This article critically examines the role of the Pakistan Studies curriculum in shaping youth perceptions of foreign policy in Pakistan. Despite extensive scholarship on historical distortions within Pakistani textbooks, limited empirical attention has been paid to how these narratives directly influence the formation of specific foreign policy attitudes among secondary school students. Employing a qualitative research design combining critical discourse analysis of federal and provincial textbooks for grades nine through twelve with a narrative reception study involving student and teacher participants, the study identifies four discursive mechanisms: the securitization of all external relations, the normalization of military-centered solutions, the systematic omission of counter-narratives, and the cartographic pre-determination of territorial postures. Findings reveal that textbooks consistently frame India as an existential foe, China as an uncritical ally, the United States as an unreliable predator, and Afghanistan through the ambiguous lens of strategic depth. Empirical reception data demonstrate that students echo these frames, expressing durable hostility toward India, unconditional trust in China, and a preference for military over diplomatic instruments. The article concludes that the curriculum creates a closed ideological loop wherein elite policy preferences shape textbooks, textbooks shape public opinion, and public opinion constrains elite policy, immunizing foreign policy from democratic reform. Critical pedagogical interventions, including multi-perspectival historical teaching and inquiry-based assessment, are proposed to break this cycle. Keywords: Pakistan Studies, Foreign Policy Perceptions, Textbook Analysis, Securitization, Military Narratives, Curriculum Reform